Psychological Harassment in the Workplace: Case-Study and Building of a New Analysis Model - Faulx, Daniel; Delvaux, Sophie; Brun, Jean-Pierre (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
From a case-study based on an analysis model, which takes into account four levels of explanation (personal, interpersonal, group and organizational), and includes the study of the interactions between these different levels, this report puts forward six observations: (1) the importance of performing the analysis on several levels, (2) the existence within harassment situations of two types of process (victimizing and conflictual), (3) the fact that these processes can co-exist at different levels of analysis, (4) the existence of interactions between processes, (5) the variability of a situation across time, and (6) the necessity of distinguishing two categories of influence involved in contextual processes. From these conclusions, the authors develop a new analysis model, which is process-based, integrative and dynamic.